Material replacement in injection molding - Dame Manalu (Universitas Riau Kepulauan, 2024)
Material replacement in a product is a fatal thing for a company, because it will have a big impact on production operations, including the regulation of machine parameters, product quality, and production costs themselves. The difference in the specifications of the two materials will have a big impact on the parameter setting of the injection molding machine including the quality of the products it produces. Therefore, finished parts from new materials must be tested first to ensure that parts with new materials have no problems during the production process or customers later.